National Resilience in Regards to Drug Problems: The Effects of Perceived Threat and Sense of Coherence: [National Resilience Dalam Masalah Narkoba: Pengaruh Perceived Threat dan Sense of Coherence] - Anita Rahma Yeni; Dicky C. Pelupessy (ANIMA Indonesian Psychological Journal, 2023)
National resilience studies discuss citizens' perceptions on the state's ability to manage and overcome national stressors. National resilience also refers to the population's feelings about the government's ability to manage the country. Drug problem is an important issue due to its potential to be a source of problems harming the state. Therefore, this study aims to describe the condition of national resilience in terms of perceived threat and sense of coherence in the context of drug problems. The participants involved were 315 individuals spread across 14 cities or regencies in West Kalimantan, recruited online with an age range of 18-57 years old (mean = 24.18). Data collection utilized survey by a questionnaire of the study instruments, being: (1) National Resilience Scale Short Version (NR-13); (2) Perceived Threat Measurement Items; dan (3) Sense of Coherence Scale - 13 (SOCS-13). Data analysis utilized multiple hierarchical regression analysis. Results of data processing show that perceived threat and sense of coherence significantly predict national resilience. Participants who feel more threatened by drugs tend to have lower national resilience level. Participants with higher sense of coherence also tend to have higher national resilience as well. From the two variables, perceived threat is stronger in the association with national resilience. This study’s findings show that the population's feelings during the crisis greatly influenced their assessment of the government's ability to overcome the crisis. Studi national resilience membahas pandangan warga negara terhadap kemampuan negara menghadapi dan mengatasi stresor nasional. National resilience juga merujuk kepada perasaan masyarakat terhadap kemampuan pemerintah mengelola negara. Masalah narkoba merupakan isu penting karena berpotensi menjadi sumber permasalahan yang merugikan negara. Maka dari itu, studi ini bertujuan menggambarkan kondisi national resilience yang ditinjau dari nilai perceived threat dan sense of coherence dalam konteks masalah narkoba. Partisipan studi sebanyak 315 individu yang tersebar di 14 kota atau kabupaten di Kalimantan Barat, yang direkrut secara daring dengan rentang usia 18-57 tahun (mean = 24,18). Pengumpulan data menggunakan metode survei dengan bantuan kuesioner instrumen studi, yaitu: (1) National Resilience Scale Short Version (NR-13); (2) Perceived Threat Measurement Items; dan (3) Sense of Coherence Scale - 13 (SOCS-13). Analisis data menggunakan analisis regresi hierarki berganda. Hasil pengolahan data menunjukkan bahwa perceived threat dan sense of coherence berhasil memprediksi national resilience. Partisipan yang merasa bahwa narkoba sangat mengancam cenderung memiliki tingkat national resilience rendah. Partisipan dengan tingkat sense of coherence tinggi juga cenderung memiliki tingkat national resilience tinggi. Dari kedua variabel tersebut, perceived threat lebih kuat berasosiasi dengan national resilience. Temuan studi ini menunjukkan bahwa perasaan masyarakat semasa krisis sangat berpengaruh terhadap penilaian masyarakat terkait kemampuan pemerintah dalam mengatasi krisis tersebut.